Commercialization of Vaccine in the News of Omicron Variant in Indonesia on Online Media - Mu’thia Mubasyira (Jurnal Multidisiplin Madani, 2023)
This research aims to analyze the commercialization of vaccines delivered in the news of Omicron variants in Indonesia on online media. This research is descriptive qualitative research using critical discourse analysis. Data from this study is vocabulary and grammar (lexicogramatics) in the news of Omicron variants in Indonesia on online media derived from news text in written online media detik.com and liputan6.com published during January 2022. The results of this study include ways detik.com and liputan6.com in constructing the commercialization of vaccines in the news of Omicron variants in Indonesia using lexical and grammatical analysis from Roger Fowler's model. Both online media use the construction of passivation grammar with the most findings. On the site detik.com found the use of this criterion as much as 14 data from 24 units of data with a percentage of 58.3%. While on the liputan6.com site found as many as 12 data from 34 units of data that included criteria for grammatical construction with a percentage of 35.3% in showing the commercialization of vaccines in the news about Omicron variants in Indonesia during January 2022. On the other hand, detik.com does not make the vocabulary of discourse battles a priority in its reporting while liputan6.com does not make marginalization vocabulary a priority in its reporting. This illustrates that each media has its own way of constructing a meaning, especially about the commercialization of vaccines that are the topic of this research